1999
DOI: 10.1212/wnl.53.8.1806
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of picture naming after repetitive transcranial magnetic stimulation

Abstract: Repetitive transcranial magnetic stimulation over Wernicke's area leads to a brief facilitation of picture naming by shortening linguistic processing time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(77 citation statements)
references
References 33 publications
5
67
1
4
Order By: Relevance
“…In the motor system, this is seen as a change in the size of MEPs in the targeted muscle. In non-motor regions, rTMS can result in changes in behavioral measures such as task performance or reaction times (e.g., Mottaghy et al, 1999;Ahn et al, 2013). Stimulation can either enhance or inhibit local neural activity (Stefan et al, 2000;Huang et al, 2005).…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…In the motor system, this is seen as a change in the size of MEPs in the targeted muscle. In non-motor regions, rTMS can result in changes in behavioral measures such as task performance or reaction times (e.g., Mottaghy et al, 1999;Ahn et al, 2013). Stimulation can either enhance or inhibit local neural activity (Stefan et al, 2000;Huang et al, 2005).…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…van der Linde, Bastiaanse, & Gilbers, 1998; Nickels, 1997;Goodglass & Kaplan, 1983). Functional brain imaging studies have suggested the importance of the left inferior parietal lobe in encoding and retrieval of episodic information (e.g., Mottaghy et al, 1999), in repeating number sequences (Cowell, Egan, Code, Harasty, & Watson, 2000), and in spatial coding of letters ( Jordan, Heinze, Lutz, Kanowski, & Jancke, 2001). Furthermore, recent functional brain imaging studies have strongly suggested that the left inferior parietal lobe has a crucial role in verbal working memory, namely phonological storage and encoding (Becker, MacAndrew, & Fiez, 1999;Paulesu, Frith, & Frackowiak, 1993).…”
Section: Training-specific Changes In Brain Responsesmentioning
confidence: 99%
“…Other studies have utilised transcranial magnetic stimulation (TMS) to transiently disrupt neural processing, thereby effectuating a quantifiable change in behavioural performance when it is applied to an area functionally involved in the task at question (Pascual-Leone et al, 2000). These studies have contributed to the understanding of the functional relevance of language-related brain areas to the behavioural execution of various language tasks (Andoh et al, 2006;Devlin et al, 2003;Mottaghy et al, 1999Mottaghy et al, , 2006Naeser et al, 2005;Nixon et al, 2004;Sakai et al, 2002;Shapiro et al, 2001). However, only few of these TMS studies employed the advantage of event-related TMS to track the exact time point of functionally relevant neural activity during language production.…”
Section: Introductionmentioning
confidence: 99%